When the Needs of Inclusive Schools Are Not Met: Differences in Science Learning Experiences for Deaf Students - Ariani, Komang Dian Indah; Riastini, Putu Nanci; Diputra, Komang Sujendra (Universitas Pendidikan Ganesha, 2025)
Every student, including deaf students, has the right to an equitable and meaningful Science learning experience. However, in practice, the specific needs of deaf students in inclusive Science classrooms have not yet been fully understood or met. This study aimed to analyze the fulfillment of physiological, safety, and love and belonging needs, which are foundational to creating an equitable Science learning experience for deaf students. This was a descriptive qualitative study with Science teachers, deaf students, and school staff at one inclusive elementary school as subjects. Data was collected through interviews, observation, and documentation, using interview guides, observation sheets, and records of learning activities. The data was analyzed qualitatively through data reduction, data display, and conclusion drawing. The findings revealed that of the three needs studied, only the need for safety had been met. This was indicated by the absence of bullying and fair treatment from teachers during Science lessons. Meanwhile, the needs for physiological well-being, as well as love and belonging, have not been met optimally. The study concludes that an equitable Science learning experience for deaf students has not yet been fully realized. The implications of these findings encourage schools and teachers to design more inclusive and responsive Science lessons that address the individual needs of deaf students.